Application of anatomically accurate, patient-specific 3D printed models from MRI data in urological oncology. Issue 6 (June 2016) - Wake, N.; Chandarana, H.; Huang, W.C.; Taneja, S.S.; Rosenkrantz, A.B.
Highlights: We examine 3D printing in the context of urologic oncology. Patient-specific 3D printed kidney and prostate tumor models were created. 3D printed models extend the current capabilities of conventional 3D visualization. 3D printed models may be used for surgical planning and intraoperative guidance.